2009
DOI: 10.1038/nmeth.1337
|View full text |Cite
|
Sign up to set email alerts
|

Protein interaction platforms: visualization of interacting proteins in yeast

Abstract: Here we describe the protein interaction platform assay, a method for identifying interacting proteins in Saccharomyces cerevisiae. This assay relies on the reovirus scaffolding protein μNS, which forms large focal inclusions in living cells. When a query protein is fused to μNS and potential interaction partners are fused to a fluorescent reporter, interactors can be identified by screening for yeast that display fluorescent foci.A variety of methods have been developed to screen for interacting proteins in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(74 citation statements)
references
References 24 publications
2
72
0
Order By: Relevance
“…The strains that conditionally express the fluorophore fusion plasmid were mated with those that conditionally express the NS fusion plasmid, and diploids were selected. Visualizations of live yeast expressing both the flurophore and NS fusions were conducted using 96-well glass-bottomed plates as described previously (48).…”
Section: Methodsmentioning
confidence: 99%
“…The strains that conditionally express the fluorophore fusion plasmid were mated with those that conditionally express the NS fusion plasmid, and diploids were selected. Visualizations of live yeast expressing both the flurophore and NS fusions were conducted using 96-well glass-bottomed plates as described previously (48).…”
Section: Methodsmentioning
confidence: 99%
“…Derivatives for mammalian expression tagged at the C terminus with Myc were generated by cloning into pcDNA3 (Invitrogen) and pBABE-puro fragments containing the coding sequence, amplified by PCR with primers that include the sequence encoding Myc. For expression of genes in yeast for analysis by the protein interaction platform assay, appropriate sequences were PCR-amplified and cloned into pDNR221, pAG416, and pBYO11 plasmids, as described previously (12).…”
Section: Methodsmentioning
confidence: 99%
“…Protein Interaction Platform Assay and Analysis-Protein interaction assays in yeast assays were performed as described previously (12). Briefly, yeast cells were co-transformed with plasmids that encode NS or NS-PDLIM7 and GFP or GFPOspE1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was the first evidence that T3SC could interact with multiple effectors and hence introduced the concept of "promiscuous" chaperones, i.e., chaperones that interact with multiple binding partners (35). In fact, a protein interaction platform assay has since revealed that Spa15 interacts with additional Shigella effectors, including IpgB2, OspB, OspC1, OspC2, OspD1, and OspD2 (for a total of nine) (67). Spa15 is involved in the efficient secretion of all nine of these effectors.…”
Section: Discovery and Classification Of T3scmentioning
confidence: 99%